Exact traveling wave solutions of generalized fractional Tzitzeica-type nonlinear evolution equations in nonlinear optics - Rezazadeh, Hadi; Batool, Fiza; İnç, Mustafa; Akinyemi, Lanre; Hashemi, Mir Sajjad (Springer, 2023)
In mathematics, physics, and engineering, establishing numerical or analytical solutions for fractional mathematical models for specific phenomena and developing fractional mathematical models for specific phenomena are important topics. In this work the (G'/G)-expansion method with the generalized fractional derivative has been used to obtained the explicit solutions of nonlinear fractional Tzitzeica type nonlinear evolution equations. These models are tested to illustrate the pertinent features of the proposed method.
Keywords: Generalized fractional derivative; (G'/G)-expansion method; Traveling wave G solutions; Nonlinear Tzitzeica type equations